Sejarah Pemikiran Ekonomi Pemikiran Ekonomi Sosialisme dalam Perkembangan Koperasi di Indonesia (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2025)
Abstract In the history of economic thought, there are two thoughts that have a strong influence in the world economic sector, namely capitalist economic thinking and socialist economic thinking. Capitalist economic thinking adheres to the understanding that the individual is above society. Meanwhile, socialism has the opposite understanding, namely that society is above the individual. This understanding of capitalism causes problems in the economy, one of which is one of the causes of poverty. In this case, cooperatives become emerging innovations that can overcome these problems. Cooperatives as business entities adhere to the understanding of socialism where society is above the individual. In its operations, the cooperative not only attaches importance to the welfare of its members but also attaches importance to the welfare of the community. In Indonesia, cooperatives have a lot of products that can provide benefits for members who are directly involved, members who are not directly involved, and the community around which the cooperative stands. As a democratic country, Indonesia has many laws and regulations related to cooperatives that are made to support the development and defense of cooperatives in Indonesia. However, the development of cooperatives in Indonesia tends to stagnate due to the evolving mindset of the community, so it is necessary to hold socialization about cooperatives to the community so that the development of cooperatives in Indonesia can continue for a long period of time. Keynotes: Cooperation, Indonesia, socialism, economics, development